Synthesis, "turn-on" fluorescence signals towards Zn2+ and Hg2+ and monoamine oxidase A inhibitory activity using a molecular docking approach of morpholine analogue Schiff base linked organosilanes. (3rd November 2022) - Singh, Gurjaspreet; Devi, Anita; Mohit,; Diksha,; Suman,; Saini, Anamika; Kaur, Jashan Deep; Gupta, Sofia; Vikas,
Abstract : A new set of morpholine analogue Schiff base linked organosilanes (5a–5c) was prepared. Abstract : A new set of morpholine analogue Schiff base linked organosilanes (5a–5c) was prepared. The prepared compounds were characterized using ( 1 H and 13 C) NMR and mass spectrometry. The sensing ability of receptor 5a was demonstrated towards different metal ions such as Ag +, Ba 2+, Ca 2+, Cd 2+, Na +, Cs +, K +, Pb 2+, Rb +, Ni 2+, Zn 2+, Hg 2+ and Co 2+ using UV-visible and Fluorescence analyses, showing good selectivity and sensitivity towards Zn 2+ and Hg 2+ in a MeOH–H2 O (9 : 1 v/v) solvent system. A "turn-on" fluorescence response towards both Zn 2+ and Hg 2+ was observed based on the collective effect of CN isomerization, intramolecular charge transfer (ICT) and chelation induced enhanced fluorescence (CHEF). Benesi–Hildebrand (B–H) plots and calibration curves were employed to measure the association constants and limits of detection, respectively. The binding mechanisms of compound 5a with Zn 2+ and Hg 2+ were confirmed using 1 H NMR and theoretically by DFT calculations. Further, molecular docking analysis was carried out against monoamine oxidase A (PDB ID-; 2BXS ) to determine the probable binding sites, giving a binding energy of −9.5 kcal mol −1 .